1996
DOI: 10.1111/j.1440-1819.1996.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between odor perception and depression in the Japanese elderly

Abstract: Odor perception has been studied in patients with various mental disorders; however, no consensus has been reached as to its detection, identification, or pleasantness/unpleasantness of odors especially in patients with depression. One hundred and nineteen normal elderly individuals living at home were exposed to odors of rose, perfume, white ginger, Indian ink, cigarette smoke, milk, feces and orange scent using the scratch and sniff method. They were asked to rate the strength of each odor, its pleasantness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
2
13
0
2
Order By: Relevance
“…It is interesting that both depression and amphetamine withdrawal in humans are associated with diminished interest in reward stimuli and accumulated data suggest potential common neurobiological substrates underlying depressive states observed in these psychiatric conditions (Paterson and Markou, 2007). While olfactory dysfunction has been reported in patients with depression (Pause et al, 2001;Satoh et al, 1996), the association of this phenomena with depressive-like symptoms related to amphetamine withdrawal remains to be evaluated. Effects of amphetamine (AMPH) administration on the dopamine (DA), DOPAC levels and DOPAC/DA ratios in the olfactory bulb (A) and striatum (B).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that both depression and amphetamine withdrawal in humans are associated with diminished interest in reward stimuli and accumulated data suggest potential common neurobiological substrates underlying depressive states observed in these psychiatric conditions (Paterson and Markou, 2007). While olfactory dysfunction has been reported in patients with depression (Pause et al, 2001;Satoh et al, 1996), the association of this phenomena with depressive-like symptoms related to amphetamine withdrawal remains to be evaluated. Effects of amphetamine (AMPH) administration on the dopamine (DA), DOPAC levels and DOPAC/DA ratios in the olfactory bulb (A) and striatum (B).…”
Section: Discussionmentioning
confidence: 99%
“…Satoh et al have found a negative relationship between the Zung Self-rating Depression Scale (SDS) scores and perceived intensities of three of eight odors in elderly Japanese men. 23 There was no correlation between the SDS scores and olfactory intensity ratings in elderly Japanese women. A single study addressed possible relationship between olfactory measures and depressive symptomatology in older, nonclinical population of European origin.…”
mentioning
confidence: 91%
“…24 The two studies did not address the problem of reliability and validity of the instruments used for the assessment of depressive symptoms. 23,24 This issue is important because somatic complaints in older subjects may be misinterpreted as representing depressive symptomatology. The BDI used in the Greek study contains several somatic items 24 and thus has been criticized as a tool for the measurement of late-life depression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[68][69][70][71] A meta-analysis of 14 published trials however concluded that serum anti-ribosomal P measurements were not sensitive in diagnosing NPSLE and did not distinguish between NPSLE subsets. [72][73][74][75][76] The few pediatric NPSLE studies so far have only demonstrated a higher prevalence of these and anti-dsDNA and anti-Sm antibodies, in childhood than adult onset SLE without any clear causal or pathogenic association yet elucidated. 4,77,78 Our group at University College London (UCL), recently described the observation that serum anti-Sm antibodies levels correlate positively with higher levels of nitrated nucleosomes, a serum marker of nitrosative stress, as measured by a novel capture ELISA.…”
Section: Autoantibodiesmentioning
confidence: 99%